A Textual Study of Turkish Overt and Null Singular Personal Pronouns in Novels - Buse Şen Erdoğan; Emine Yarar (Discours)
This study examines how Turkish overt and null singular subject pronouns are used in fiction novels. These pronouns are analysed focusing on their antecedents using the framework of Mira Ariel’s Accessibility Theory. A self-compiled corpus was created which contains 300 sentences taken from 12 novels written in Turkish. The antecedents and the overt and null forms of the singular subject pronouns are coded for the dimensions of recency, givenness, and syntactic prominence. The data collected were analysed using the Mann-Whitney U and the Chi-square tests. The findings indicate that the dimensions of recency, givenness, and syntactic prominence have different effects on the utilization of these singular pronouns. For instance, the use of the overt and null 3rd person pronouns is influenced by both recency and syntactic prominence. It is found that the givenness dimension affects the 1st person pronouns but not the 2nd or 3rd person pronouns. Both forms of the 2nd person pronouns are not controlled by these dimensions. The findings of the study suggest that not all personal pronouns are the same concerning the effects of discourse. It is also seen that of three singular person pronouns the one which is more open to such effects is the 3rd person pronouns in Turkish. These findings clearly confirms that the dimensions of recency, givenness, and syntactic prominence are subject to cross-linguistics variance which should be taken into consideration while studying discourse coherence through pronouns.